Development of adult education - Buntine, M. A. (The University of Edinburgh, 1925)
I. INTRODUCTORY - Early efforts to establish Adult education - philanthropy - great educationalists of the Nineteenth Century. pp 1 - 36. • II. THE INFLUENCE OF THE MECHANICS' INSTITUTIONS. pp.37 - 56. • III. THE CONTINUATION SCHOOL SYSTEM - rise of technical schools - establishment of Department of Education. pp.57 - 82. • IV. UNIVERSITY EXTENSION. pp.83 - 105. • V. WORKERS' EDUCATIONAL ASSOCIATION. pp.106 - 135. • VI. RECENT DEVELOPMENTS - W.E.A. work Continued - education within factories - Birmingham University and Trade Unions - Misfits in industry. pp.136 - 154. • VII. ADULT EDUCATION ABROAD - European Countries - America - The Colonies - Australia - Conclusion. pp.155 - 177.

In conclusion one might add that although there yet remains a great deal to he done in the educational world, yet education alone and unaided can never bring about the longed-for reforms which many enthusiasts would claim. Education alone can never raise to a high level the standard of living of certain classes. We no longer believe with Socrates that knowledge is virtue. Indeed education alone can never affect to any great degree those who are apathetic, who do not spontaneously take advantage of what it offers. All that can be done in the realm of adult education is to provide a means to betterment mentally, morally, and physically for those who will of their own accord accept of it. Education can never be thrust upon adults. It must be provided in response to a spontaneous demand. In that respect therefore, adult education depends upon primary and secondary education. If they are unsuccessful adult education is almost an impossibility. Again, if education is to achieve anything very much it must co-operate with other arts and sciences which have to deal with human beings. "At present the educational campaign to direct our energies to better advantage is carried on by various field services, which, working without any knowledge of the general purpose and scope of other operations, are marked by much confusion of intention and enormous waste of energy. The responsibility for this disadvantage must lie in the patch-work character of most of our schemes of educational reform, social improvement and betterment of living conditions. Real progress towards such betterment demands a biological point of view, and intensive co-operation in the numerous departments of research. The word life should be associated with words suggesting the commonest phases of human behaviour - home, school, college, social and political life,the life of the courts, prisons, reformatories, and of individual persons and groups, such as the life of a community, nation and race.